Implementation of LCM (Linear Congruent Method) Method in Region Song Game - Addinul Arfansyah Harahap; Nelly Astuti Hasibuan (The IJICS (International Journal of Informatics and Computer Science), 2020)
The Regional Song Game is a game that educates players to hone the ability of knowledge about folk songs in the form of questions given the Regional Song game. With the game Regional Songs, players can expand the ability of players about the knowledge of regional songs. Aside from being a means of entertainment, games can also be an exciting learning medium and do not make players bored, so it becomes a pleasant learning atmosphere. The linear congruent method (LCM) is a random number generator method that is widely used by computer programs. The application of the Linear Congruent Method (LCM) in the Regional Song game is intended to randomize the questions that will be displayed by the Regional Song game. Regional Songs Game is an application designed to provide insights about folk songs for the players. This game aims to reintroduce folk songs to the people lost by the ages.